2006
DOI: 10.1111/j.1475-4762.2006.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Sacred cows in coastal management: the need for a ‘cheap and transitory’ model

Abstract: The participative, ‘bottom‐up’ approaches of contemporary European ICZM (integrated coastal zone management) are ineffectual and unsustainable. The approach lacks the authority and resources to deliver ICZM and should be abandoned. A new model of ICZM in a predominantly sectoral administrative framework is presented. It requires that capacity be built in existing statutory authorities and in‐house ICZM groups be established. Time‐limited participatory projects would be used to gain information on conflicts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 10 publications
0
30
0
3
Order By: Relevance
“…Research by McKenna and Cooper (2006) argued that participative, 'bottom-up' approaches are ineffectual and unsustainable because they lack authority and resources. They further reasoned that a sound statutory and legislative basis is needed for effective coastal management.…”
Section: Commitment From Policy Makersmentioning
confidence: 98%
“…Research by McKenna and Cooper (2006) argued that participative, 'bottom-up' approaches are ineffectual and unsustainable because they lack authority and resources. They further reasoned that a sound statutory and legislative basis is needed for effective coastal management.…”
Section: Commitment From Policy Makersmentioning
confidence: 98%
“…Whilst there is much 'common sense' in the ICZM principles, it could be suggested that they are merely a repackaging of many of the principles of good environmental governance, commonly used in other spheres of environmental management. Their detailed interpretation at an operational level within an ICZM context has also been problematic and has led to much debated in the academic literature (for example, Cooper and McKenna 2008;McKenna and Cooper 2006;. Even the widely accepted principle of 'working with natural processes, Cooper and McKenna (2008) note can be interpreted in various ways according to the time frame adopted.…”
Section: Iczm Performance and The Management Of Coastal Riskmentioning
confidence: 99%
“…This progression towards legal responsibility and agenda-setting is occurring in many parts of the world (WHO, 2011) and coastal managers must therefore consider the implications and allow all users, regardless of their difficulties, to experience the same level of coastal involvement as the general population. Legislative support is a vital corollary for effective coastal policy implementation (McKenna & Cooper, 2006), and hence LD statutory frameworks need effective policy action.…”
Section: Introductionmentioning
confidence: 99%